The Effect of Stress Ball on Anxiety and Pain Levels in Angiography: A Randomized Controlled Trial - Dilan Yüksel; Dilek Güneş (Cardiovascular Therapeutics)
Conclusion: The application of stress balls during angiography was associated with decreased anxiety and pain levels in patients. Stress ball intervention may serve as a beneficial adjunct to pharmacological treatments. This study underscores the potential of nonpharmacological interventions in enhancing patient comfort during invasive procedures.